Recent advances in research on common targets of neurological and sex hormonal influences on asthma - Wenting Zhou; Huan Chen; Xinyu Chen; Jing Gao; Wenting Ji (Clinical and Translational Allergy)
Abstract Background Asthma is currently one of the most common of respiratory diseases, severely affecting the lives of patients. With the in‐depth study of the role of the nervous system and sex hormones on the development of asthma, it has been found that the nervous system and sex hormones are related to each other in the pathway of asthma. Objective To investigate the effects of sex hormones and the nervous system on the development of asthma. Methods In this review, we searched for a large number of relevant literature to elucidate the unique mechanisms of sex hormones and the nervous system on asthma development, and summarized several common targets in the pathways of sex hormones and the nervous system on asthma. Conclusion We summarize several common important targets in the pathways of action of sex hormones and the nervous system in asthma, provide new directions and ideas for asthma treatment, and discuss current therapeutic limitations and future possibilities. Finally, the article predicts future applications of several important targets in asthma therapy.